Evaluation of Physical Education Program through Intracurricular, Co-curricular, Extracurricular Activities at Junior High Schools in Tuban District (Journal of Physical Education and Sports, 2020)
The purpose of this study was to analyze and describe the context evaluation, input evaluation, process evaluation, and product evaluation of the physical education program through intracurricular, co-curricular, extracurricular activities at junior high schools in Tuban District, Tuban Regency. This research is a program evaluation using the CIPP evaluation model, namely context, input, process, and product. This research data collection techniques carried out by observation, interview and documentation methods. Qualitative data analysis techniques with four components, namely: data collection, data reduction, data presentation, drawing conclusions. The results of the study were Context on intracurricular activities, extracurricular activities were carried out well. Inputs in intracurricular, extracurricular activities are appropriate and there are obstacles in the infrastructure. The process of intracurricular and extracurricular activities went well. Product, good achievement in intracurricular, extracurricular activities. In the context, input, process, product, co-curricular activities have not been going well. The conclusion is that the context on intracurricular, extracurricular activities with complete tools, objectives, program policies is implemented well. Inputs in intracurricular, extracurricular activities are making and collecting devices used and lacking infrastructure. The process of intracurricular activities, extracurricular implementation and coordination are carried out according to the schedule, material and implementation process, for lack of infrastructure. The intracurricular products are in accordance with the KKM, extracurricular achievements, namely the district, provincial and even national levels. The co-curricular activities of several schools did not implement and were not optimal.